2008
DOI: 10.1159/000150977
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Reduces Aldosterone, Upregulates Adrenal Angiotensin II AT<sub>2</sub> Receptors and Normalizes Adrenomedullary Fra-2 in Ovariectomized Rats

Abstract: We studied the effect of ovariectomy and estrogen replacement on expression of adrenal angiotensin II AT1 and AT2 receptors, aldosterone content, catecholamine synthesis, and the transcription factor Fos-related antigen 2 (Fra-2). Ovariectomy increased AT1 receptor expression in the adrenal zona glomerulosa and medulla, and decreased adrenomedullary catecholamine content and Fra-2 expression when compared to intact female rats. In the zona glomerulosa, estrogen replacement norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 122 publications
4
41
1
Order By: Relevance
“…This finding is in correspondence with the results obtained with nonimmuno-based methods like Angiotensin II receptor binding (Macova et al 2008), and in situ hybridization using specific riboprobes (Jöhren et al 1995). Western blot analysis using the same antibody revealed a single intensive band in the DRGs at the identical molecular weight as was found in the adrenal gland (Fig.…”
Section: Resultssupporting
confidence: 89%
“…This finding is in correspondence with the results obtained with nonimmuno-based methods like Angiotensin II receptor binding (Macova et al 2008), and in situ hybridization using specific riboprobes (Jöhren et al 1995). Western blot analysis using the same antibody revealed a single intensive band in the DRGs at the identical molecular weight as was found in the adrenal gland (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Binding of Ang II to the widely expressed AT 1 R plays a predominant role in the capacity of the adrenal zona glomerulosa (ZG) to produce aldosterone (Capponi 2004, Schiffrin & Touyz 2004, Hunyady & Catt 2006 via cytochrome P450 aldosterone synthase (P450aldo; Bassett et al 2004, Capponi 2004. In contrast to several adult tissues, AT 2 R is relatively highly expressed in the adult adrenal glands (ZG and medulla; Breault et al 1996, Frei et al 2001, Macova et al 2008. In various pathological situations, it is generally assumed that Ang II stimulation of the AT 2 R counteracts the effects of AT 1 R (de Gasparo et al 2000, Schiffrin & Touyz 2004.…”
Section: Introductionmentioning
confidence: 99%
“…29 Estrogens also stimulate renin release from the juxtaglomerular cells through estrogen receptor-α (ERα), 30 whereas endogenous estrogens exert inhibitory effects on the RAAS. 28,29 Experimental studies have shown that circulating levels of aldosterone increase after menopause and that estrogen therapy blunts this increase [31][32][33][34][35] ; however, corresponding data in humans are lacking.…”
Section: Estrogens and The Raasmentioning
confidence: 99%
“…In line with this proposition, it was found that E2 decreases aldosterone levels and the response of aldosterone to angiotensin II in ovariectomized female rats. 33,34 Although the expression of ERβ and GPER-1 was not investigated, it could be that E2 inhibits the GPER-1-mediated secretagogue effect of E2. Moreover, ovariectomy was associated with increased BP, long-term mortality, and plasma aldosterone; the latter was prevented by E2 or phytoestrogens.…”
Section: Adrenocortical Ers and Primary Aldosteronismmentioning
confidence: 99%